A comparative study of the mastery of fundamental movement skills between different cultures - dos Santos, Fernando Garbeloto (2016)
It has been suggested that guidance, encouragement and opportunity are crucial factors for children’s motor development. They are especially important to promote the mastery of fundamental movement skills. The present study investigated the association between two elements related to those factors – proposed curriculum of physical education and the most popular sport in a given country – and the incidence of mastery in the FMS in children from 4 to 10 years of age. In order to carry out a cross-cultural comparison, three studies from different countries (Portugal, China and USA) that used TGMD-II were selected. The results indicated association between proposed curriculum and the number of children mastering FMS. This association increases in older age groups of children from USA, the most structured curriculum related to FMS, presenting the highest average percentage of mastery.  Additionally, we did not find association of the most popular sports in a given country with the mastery of the related skill. These results are interpreted as evidence for the importance of guidance on the mastery of FMS.